1. Estimation of Dog Population and Owner Knowledge Toward Rabies Risk of Dog in Padang Ganting Sub-district - Taufikah Rahmah; T Reza Ferasyi; Razali Razali; Muhammad Hambal; Rastina Rastina; Rusli Rusli (Universitas Syiah Kuala, 2017)
The aim of this research was to calculate an estimated population of dogs, dog population ratio comparison against their area, the household, the number of owners, and the gender as well as to find out the level of knowledge towards risk of rabies to dog owners at Jorong in Padang Ganting Sub-district. The respondents were the people at 4 jorong Padang Ganting Sub-district who kept the dogs at home and willing to be interviewed. This research was conducted in the form of field surveys. Data was collected by interviewing people who rose the dogs using a form and a structured questionnaire. Data retrieval was composed of secondary and primary data. Secondary data was taken from the animal husbandry and fisheries at Tanah Datar district. Data were analyzed using descriptive methods. The results showed that the population of dogs at 4 ellipse were the ellipse Koto Gadang Hilir, Koto Alam, Koto Gadang, Rajo Dani were 140, 117, 124, 115. There were any differences between the number of households with dog owners, the number of households with dogs, the number of dogs with owners dogs, and area with dogs, male and female dogs, a male dog with dog owners, a female dog with dog owners. Respondents generally maintained more than one dog with rearing cages. The purpose of maintenance dog was a hunting dog and gave the vaccination. From this research, also known the knowledge of the owner to the risk of rabies at Padang Ganting Sub-district and good in categories